IMPLEMENTASI PROGRAM KAMPUS MENGAJAR TERHADAP PENINGKATAN LITERASI & NUMERASI PESERTA DIDIK SD NEGERI 2 SUMBERAGUNG - Nadiah, Cici; Rigianti, Henry Aditia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this research is to improve literacy and numeracy skills through the Teaching Campus program. The program involves students who teach in schools in designated areas, who face challenges in increasing literacy and numeracy in each school. The method applied in this program is through an interactive and participatory approach. Students collaborate with the principal, teachers at school to design and implement creative and interesting learning. Using a variety of concrete materials and existing resources to increase students' interest and understanding of literacy and numeracy. This service activity was carried out at SD Negeri 2 Sumberaguang Nogosari Sumberagung in Jetis District, Bantul Regency, Yogyakarta Province. This activity lasted for four months from 19 February 2024 to 19 June 2024. The final results of the Mengajar campus program significantly increased the literacy and numeracy skills of students at SD Negeri 2 Sumberagung. After four months of implementation, there was an increase in the average literacy score of 71.9% compared to the previous 53.5%, and the numeracy score increased by 71.2%, based on the results of the pre-test and post-test. Apart from that, student participation in carrying out literacy and numeracy activities also increased significantly, showing high student interest. The Teaching Campus program provides many opportunities for students to make useful contributions to basic education, and students benefit from innovative learning that focuses on improving literacy and numeracy. Keywords: Literacy Skills, Numeracy Skills, Teaching Campus, Elementary School